PERANCANGAN POWER BANK DENGAN MENGGUNAKAN DINAMO SEPEDA SEDERHANA - Alfi Ridwanto; Wisnu Broto (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
One of the problems that often arise when in the course of using a bicycle is the battery smartphone that runs out before the destination. Therefore, the dynamo of a bicycle is a device that converts the energy of motion into electricity that comes from the rotation of tires that occur during the streets. Since the source of the dynamo is the tire rotation, the output of the dynamo is unstable due to the changing speed. So we need an energy storage to hold the electrical energy. The power bank is a device used to store energy from the dynamo and is used to transfer payloads to Smartphones and mobile phones. Keywords: Smartphone, Power bank, Electric